Experimental study of welded joints on steel plate cold-rolledsheet metal using different electrode tips - Omar, N.I.; Rasi, R.Z.R.; Zainudin, M.H.F.; Azhari, M.A.; Yusuf, Y.; Mustafa, N.; Azlan, U.A.; Razi, M.H.F.A.; Ismail, S.; Mohamad, S. (UNIVERSITI TEKNIKAL MELAKA, 2018)
Resistance spot welding is commonly used in the automotive industry, because it has advantages such as high speed, high-production assembly lines and suitability in automation. Welded joints are exposed to varying loads and pressure, as such, these conditions cause the joints to rupture. The objective of this paper is to study the different properties of welded joints in Steel Plate Cold-Rolled Coils, SPCC sheet metal by using different electrode geometries. The material used in this study was SPCC and selected welding tips: dome nose and flat nose as they are widely used in industrial applications. The findings indicated that weld nuggets of SPCC using the dome nose welding tip showed a value nearest to the theoretical value based on the America Welding Society, AWS’s formula. The results for tensile testing were in accordance with weld nugget size, and the dome nose welding tip was 10% stronger than the flat nose. The difference in electrode geometries showed a significant impact on welded joint properties of SPCC metal for automotive applications.